2012
DOI: 10.1016/j.bone.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 acts directly on renal proximal tubules to induce phosphaturia through activation of the ERK1/2–SGK1 signaling pathway

Abstract: Fibroblast growth factor-23 (FGF23) is a bone-derived endocrine regulator of phosphate homeostasis which inhibits renal tubular phosphate reabsorption. Binding of circulating FGF23 to FGF receptors in the cell membrane requires the concurrent presence of the co-receptor αKlotho. It is still controversial whether αKlotho is expressed in the kidney proximal tubule, the principal site of phosphate reabsorption. Hence, it has remained an enigma as to how FGF23 downregulates renal phosphate reabsorption. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 27 publications
5
150
4
Order By: Relevance
“…A recent study showed that FGF-23 directly downregulates membrane expression of the renal NaPi2a (SLC34A1). 25 Reduction of FGF-23 and concomitant reduction of the renal phosphate fractional excretion have previously been observed in clinical studies in patients with CKD treated with P binders. 26,27 The reduced P intestinal intake mechanism posited for tenapanor is supported by the robust attenuation of ectopic deposition of Ca and phosphate (presumably as hydroxyapatite) in the aortic arch and stomach in tenapanor-treated rats (Figure 8).…”
Section: Discussionmentioning
confidence: 81%
“…A recent study showed that FGF-23 directly downregulates membrane expression of the renal NaPi2a (SLC34A1). 25 Reduction of FGF-23 and concomitant reduction of the renal phosphate fractional excretion have previously been observed in clinical studies in patients with CKD treated with P binders. 26,27 The reduced P intestinal intake mechanism posited for tenapanor is supported by the robust attenuation of ectopic deposition of Ca and phosphate (presumably as hydroxyapatite) in the aortic arch and stomach in tenapanor-treated rats (Figure 8).…”
Section: Discussionmentioning
confidence: 81%
“…Although this may seem to be counterintuitive, it is important to note that the activity of the ERK pathway is tissue and cell type dependent (38). The ERK pathway regulates a wide array of physiologic and pathologic processes, including proliferation, development, and metabolism, and while in the kidneys, as a downstream effector of FGF23 signaling, it participates in regulating phosphorus homeostasis (39), in cancer cells it enhances proliferation as a downstream effector of multiple growth factors, including IGF-1 (40). Furthermore, the effect of klotho on various Only KL1 domain suppresses IGF-1 signaling and interacts with the IGF-1R in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…NHERF1 assembles a ternary complex with NPT2A and ezrin, thereby linking the transporter to the actin cytoskeleton. NHERF1 is essential for the inhibitory action of PTH and FGF23 on phosphate transport (12,17,20). NHERF1-null mice and humans harboring mutations in SLC9A3R1 exhibit pronounced phosphate wasting, nephrolithiasis, and skeletal dis-* This work was supported by National Institutes of Health Grants DK069998 and DK105811 (to P. A. F.), DK101484 and DK100357 (to O.…”
mentioning
confidence: 99%